The Semiotics of Sambal: Food, Domestic Intimacy, and Symbolic Boundary-Making in Indonesian Short Fiction - ‘Asyuro, Aniqo Dhamar; Oktaviana, Rachelina Mariska; Atikurrahman, Moh (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article aims to examine how sambal functions as a culinary sign in two Indonesian short stories, Puthut's Sambal Keluarga and Tenni Purwanti's Sambal di Ranjang. Rather than treating sambal as a minor condiment, this study reads sambal as a dense cultural code through which domestic intimacy, gendered labor, and symbolic boundaries are narrated. This research uses a qualitative comparative textual design based on close reading, document analysis, and theory-guided coding. Three conceptual lens structure analysis: Roland Barthes's semiology, especially denotation, connotation, myth, and lexia-based reading; gastrocriticism, which approaches food as a social and affective text; and commensality, which explains how shared eating organizes membership, proximity, and exclusion. Findings show that in Sambal Keluarga, sambal consolidates familial myth through ritual breakfast, affective repetition, and insider knowledge, while in Sambal di Ranjang, it is privatized as a sign of ideal wifehood, erotic service, and conjugal possession before being reclaimed as a medium of resistance and economic autonomy. By combining semiotics with food studies, this study demonstrates that ordinary culinary objects can serve as rigorous evidence for analyzing family myth, domestic power, and the politics of inclusion in literary texts.